Alternate treatments of jacobian singularities in polar coordinates within finite-difference schemes - Bruno-Alfonso, Alexys [UNESP]; Cabezas-Gómez, Luben; Navarro, Helio Aparecido (My University, 2012)
Jacobian singularities of differential operators in curvilinear coordinates occur when the Jacobian determinant of the curvilinear-to-Cartesian mapping vanishes, thus leading to unbounded coefficients in partial differential equations. Within a finite-difference scheme, we treat the singularity at the pole of polar coordinates by setting up complementary equations. Such equations are obtained by either integral or smoothness conditions. They are assessed by application to analytically solvable steady-state heat-conduction problems.
Keywords: Finite difference; Jacobian determinant; Polar coordinates